PERANCANGAN DAN ANALISIS PENGUJIAN KONDUKTIVITAS PANAS PADA TIPE MATERIAL PADAT - Saputraa, Ardhii; Samhuddin, Samhuddin; Hasanudin, La (Teknik Mesin Universitas Halu Oleo, 2022)
Thermal conductivity is the ability of a materal to transmit heat from one place to another. The value of thermal conductivity is important to determine the type of good heat conductor and bad heat conductor. But the problem is how to know the value of the thermal conductivity of varios materials.This study aims to determine the value of the conductivity of various solid materials. The test is carried out using the research layout tool. The results of research conducted from various solid materials based on the value of the highest heat transfer area are found in composites with a value of 24.0349 cm2. The largest value of the melting ice flow rate with differential temperature was found in the brass sample with a value of 0.075 gr/s and the lowest in the composite sample with a value of 0.017 gr/s. The highest thermal conductivity value is found in the iron sample with a value of 0.358147 W/m k and the lowest is in the composite sample with a value of0.107522 W/m k.Keywords: Conductivity, Heat Transfer Rate, Differential Temperature